Alternativas africanas ao desenvolvimento ao impacto da globalização - notas críticas soltas - Castel-Branco, Carlos Nuno (Desafios para Moçambique 2022, 2022)
ALGUNS GRANDES DESAFIOS ACTUAIS PARA O DESENVOLVIMENTO EM ÁFRICA Há uma série de grandes desafios para transformação social, política e económica no continente africano que têm de ser enfrentados. Primeiro, é necessário passar da adopção e aplicação de “receitas” de desenvolvimento político, social e económico, frequentemente até irrelevantes para as questões de desenvolvimento que dizem tratar, para uma abordagem de economia política do desenvolvimento enraizada na análise das condições históricas, sociais, políticas e económicas concretas do continente, de cada país e do ambiente internacional de que fazemos parte. Segundo, a nova corrida a (scramble for) África mobiliza apaixonados debates e aspirações, particularmente por parte de forças dos capitais nacionais que já se posicionam para beneficiar dos influxos de capital que estão a ocorrer. Terceiro, em relação com a nova corrida a África, surge o problema da integração subregional, formal e real, e a luta pelas hegemonias sub-regionais (como é o caso, por exemplo, das pretensões hegemónicas da África do Sul na África Austral e em todo o continente). Quarto, há factores demográficos fundamentais que têm de ser tomados em consideração nas opções de desenvolvimento para o futuro, nomeadamente resultantes (i) dos ritmos e dinâmicas de urbanização; e (ii) do impacto das grandes epidemias e endemias (como o HIV/SIDA, malária e outras) nas estruturas e dinâmicas da força de trabalho e do mercado do trabalho, nas opções tecnológicas, na organização social da produção, no ambiente de investimento e nos custos sociais e natureza dos serviços de saúde e assistência social. Quinto, mudanças climáticas são parte essencial da problemática do desenvolvimento global e continental. Sexto, como podem os processos de desenvolvimento no continente passar do foco tradicional em produtos (biocombustíveis, café, cacau, chá, algodão, etc.), recursos naturais e serviços isolados uns dos outros para dinâmicas de criação e desenvolvimento de capacidades e actividades articuladas, inovadoras e diversificadas?
Keywords: *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - portuguese / português; economic development / desenvolvimento económico; society / sociedade

The Importance of Microfinance for Development of MSMEs in ASEAN: Evidence from Indonesia - Tambunan, Tulus (Journal of ASEAN Studies, 2014)
Despite studies on microfinance (MF) or development of microfinance institutions (MFIs) in Asia developing countries, including countries as member states of the Association of Southeast Asian Nation (ASEAN), are growing, not so much attention have been given to the role of MF in financing micro, small and medium enterprises (MSMEs). Based on a key literaturestudy and analysis of secondary/national data, the main aim of this study is to fill this gap. It shows that in many ASEAN member states (AMS) MF has developed to some significant degree, although the rate of growth (e.g. number of MFIs, number of depositors and debtors, total loans allocated, etc.) as well as the market structure of MF vary across member states. From the Indonesian case this study comes with two most interesting facts. First, majority of MSMEs do not have access to credit from banks and/or other formal non-bank financial institutions. Second, MF services or MFIs are growing fast, and the most popular MF program so far is Kredit Usaha Rakyat (KUR), or people business credit (i.e. a credit scheme without collateral), introduced during the SBY period
Number: 2
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico

Indonesia After the Asian Crisis* - Hill, Hal; Shiraishi, Takashi (Asian Economic Policy Review, 2007)
Indonesia was deeply affected by the 1997–1998 crisis, more so than its East Asian neighbors. Its economic contraction was deeper and more prolonged. It was the only one to experience a (temporary) loss of macroeconomic control. It also suffered “twin crises,” in the sense that its serious economic and financial problems were accompanied by regime collapse. Consequently, recovery was a slow and complex process, as new institutions had to be created, and old ones reformed under successive short-lived administrations. But this process is largely over. The directly elected president with a strong popular mandate is in power. The new institutional framework for economic policy-making is in place. Macroeconomic stability has been restored. Although growth has yet to return to pre-crisis levels, by 2004 per capita income and poverty incidence had recovered to levels prevailing in the mid-1990s, and in the circumstances economic recovery has arguably proceeded about as quickly as could reasonably have been expected.
Number: 1 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1748-3131.2007.00058.x
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; economic development / desenvolvimento económico

The Indonesian Financial Crisis: From Banking Crisis to Financial Sector Reforms, 1997-2000 - Sharma, Shalendra D. (Cornell University Press, 2001)
In mid-1998, a World Bank study grimly noted that "Indonesia is in deep economic crisis. A country that achieved decades of rapid growth, stability, and poverty reduction is now near economic collapse . . . no country in recent history, let alone one the size of Indonesia, has ever suffered such a dramatic reversal of fortune." There is bitter irony in Indonesia's fall from grace. Long hailed as a model of successful economic development, it was widely predicted to escape the fate of Thailand. Between June-August 1997, as Thailand's economy unraveled and the virulent Asian flu sent shock waves through the region, the Indonesian economy remained relatively stable—a veritable rock in the stormy sea. Even the World Bank remained upbeat about the short-term outlook, believing that a widening of the intervention band would be sufficient to ward off contagion.4 The Indonesian government, which received much praise for its swift and decisive response to the crisis, went to great lengths to assure jittery investors "that Indonesia was not Thailand." Then the unthinkable happened. Indonesia suddenly succumbed to the contagion, and, measured by the magnitude of currency depreciation and contraction of economic activity, it emerged as the most serious casualty of Asia's financial crisis. What happened? Why did Indonesia (and the other high-performing Asian economies) collapse like hollow dominoes? In the numerous post-mortems that have followed, analysts have identified a number of related factors behind the region's dramatic reversal of fortune. In the case of Indonesia, the variable that soon acquired particular salience was "crony capitalism." Initially popularized by the Economist, the term quickly took a life of its own. Soon thereafter, the distinguished MIT economist, Paul Krugman, would argue that crony capitalism lay the root of Indonesia's—and indeed, East Asia's—financial woes. Krugman describes the innerworkings and manifestations of the insidious crony capitalism in evocative prose.
Number: 71 Publisher: Southeast Asia Program Publications at Cornell University
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico